The Pre-Eminence of Theory versus the European CVAR Perspective in Macroeconometric Modeling - Aris Spanos (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
The primary aim of the paper is to place current methodological discussions in macroeconometric modeling contrasting the 'theory first' versus the 'data first' perspectives in the context of a broader methodological framework with a view to constructively appraise them. In particular, the paper focuses on Colander's argument in his paper 'Economists, Incentives, Judgement, and the European CVAR Approach to Macroeconometrics' contrasting two different perspectives in Europe and the US that are currently dominating empirical macroeconometric modeling and delves deeper into their methodological/philosophical underpinnings. It is argued that the key to establishing a constructive dialogue between them is provided by a better understanding of the role of data in modern statistical inference, and how that relates to the centuries old issue of the realisticness of economic theories.
Keywords: B4; C1; C3; 330; Econometric methodology; 'general-to-specific'; pre-eminence of theory; cointegrated VAR; statistical adequacy; realisticness of a theory; Ökonometrisches Makromodell; Wissenschaftliche Methode; VAR-Modell; Theorie